1998
DOI: 10.1007/s002689900436
|View full text |Cite
|
Sign up to set email alerts
|

Redifferentiation Therapy with Retinoids: Therapeutic Option for Advanced Follicular and Papillary Thyroid Carcinoma

Abstract: During the course of tumor progression the differentiated morphologic and functional characteristics of differentiated thyroid carcinomas (DTC) disappear. This corresponds to more aggressive growth, metastatic spread, and loss of iodine uptake. Experimental data give strong evidence that differentiated functions of iodine metabolism can be reinduced by retinoic acids. Results of a study performed in patients with advanced DTC are presented. Twenty patients with DTC (eight follicular, seven papillary, five oxyp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
68
1
5

Year Published

1998
1998
2011
2011

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 132 publications
(77 citation statements)
references
References 28 publications
3
68
1
5
Order By: Relevance
“…Thyroid cancer requires high levels of TSH to induce or to maximally stimulate 131 I uptake (1). In some differentiated thyroid cancer, treatment with retinoic acid (RA), in addition to TSH stimulation, has been reported to induce NIS mRNA expression (9) and NIS activity (10). The results of clinical pilot studies have suggested that iodide uptake may be stimulated by RA treatment into metastases of thyroid cancer that do not take up 131 I under standard treatment conditions (10).…”
mentioning
confidence: 99%
“…Thyroid cancer requires high levels of TSH to induce or to maximally stimulate 131 I uptake (1). In some differentiated thyroid cancer, treatment with retinoic acid (RA), in addition to TSH stimulation, has been reported to induce NIS mRNA expression (9) and NIS activity (10). The results of clinical pilot studies have suggested that iodide uptake may be stimulated by RA treatment into metastases of thyroid cancer that do not take up 131 I under standard treatment conditions (10).…”
mentioning
confidence: 99%
“…In the first clinical trial for RA, Simon et al described an increase in RI uptake of thyroid cancer cells in 40% (4/10) of patients [9]. Likewise, other initial clinical trials also reported that about 40-50% of RI-refractory patients showed an increase in RI uptake [10][11][12]. However, the following clinical trials reported much lower rates of RI uptake increase.…”
Section: Retinoic Acidsmentioning
confidence: 88%
“…They have prompted a multicentric clinical study to test the potential of retinoids for a redifferentiation therapy of thyroid cancer. So far, 75 patients with poorly differentiated, inoperable thyroid cancer and absent or insufÂźcient iodide uptake have been included (69,70). They were treated with oral doses of 1.0±1.5 mg 13-cis-RA per kg body weight and day.…”
Section: Retinoic Acid Redifferentiation Therapymentioning
confidence: 99%